Swimming Up Niagara Falls! The Battle to Get Disability Rights Added to the Canadian Charter of Rights and Freedoms - Lepofsky, M. David (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2023)
This is the personal memoir of blind lawyer and volunteer disability rights advocate David Lepofsky. It describes his involvement in and perspectives on the successful fight from 1980 to 1982 to get Canada’s proposed Charter of Rights amended to guarantee equal rights for people with disabilities. It includes a foreword by the Hon. Rosalie Abella, former Justice of the Supreme Court of Canada. This memoir recounts the little-known saga of the disability amendment to the Charter. Few know that equality for people with disabilities was the only constitutional right added to the Canadian Charter of Rights and Freedoms during the widely publicized eighteen-month battle over the patriation of Canada’s Constitution, from October 1980 to April 1982. It is aimed at anyone interested in disability rights, human rights, Canadian political or legal history, social justice advocacy, and Canadian constitutional law. It provides a mix of legal and legislative history, personal autobiography, grassroots advocacy strategy and reflective commentary on lessons learned. It compares social justice advocacy techniques in 1980 to those practiced in the disability rights arena four decades later.